ORGANIZING THE INDEPENDENT WORK OF STUDENTS IN MEDICAL HIGHER EDUCATION INSTITUTIONS EFFECTIVELY THROUGH INFORMATION TECHNOLOGIES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In the contemporary educational paradigm, information technologies (IT) occupy a central role in introducing innovative approaches to organizing students’ independent learning activities. This study is dedicated to a comprehensive exploration of the didactic and technological possibilities of effectively organizing students’ independent work in medical higher education institutions through the use of IT tools. The article analyzes the integration of digital platforms, virtual simulation technologies, artificial intelligence-based analytical tools, and interactive learning environments into the educational process. The research findings confirm the high efficacy of IT tools in enhancing students’ cognitive competencies, personalizing the learning process, strengthening clinical skills, and optimizing the administrative workload of instructors. This work underscores the strategic importance of IT in modern medical education and highlights the critical role of digital transformation in preparing future healthcare professionals.